Analysis of Socio-Economic Conditions of Extreme Poor Communities: Survey Study in Medalsari Village and Sinarjaya Village, Pandeglang Regency - Ariyan, Said; Roml, Ombj (Future Science, 2025)
This study aims to analyze the socio-economic conditions of extreme poor communities in Medalsari Village and Sinarjaya Village, Pandeglang Regency. This topic was raised to understand the factors that influence extreme poverty in both villages and to identify effective mitigation strategies based on local conditions. Another reason for choosing this theme is that the village with the highest level of extreme poverty in Pandeglang, which requires a strategic and effective approach to get out of the extreme poverty zone and reduce its impact. The research method used is a quantitative method with a survey technique. Data were collected through questionnaires distributed to respondents totaling 117 Heads of Families for Sinarjaya Village, and 139 Heads of Families for Medalsari Village which came from P3KE Bappeda Pandeglang Regency data. This survey involved aspects such as income, education level, access to basic services, and employment conditions. The research findings show that there are still households that are not categorized as extremely poor, most heads of families work in the informal sector (laborers and farmers) with limited skills and experience, social support in the form of government assistance has not fully covered their basic needs, families try to cover the shortfall through alternative businesses and rely on social assistance, although the potential productivity of family members can still be increased. The impact of this research is expected to provide more targeted and data-based policy recommendations to reduce extreme poverty in Pandeglang Regency. These findings are also expected to be a reference for stakeholders in designing more effective and sustainable poverty alleviation programs.